Ownership of assets in Chinese shipping funds - Hai Jin; Orestis Schinas (International Journal of Financial Studies, 2019)
As the importance of Chinese financial schemes in maritime business increases, and many issues on the ownership of the assets under the current Law remain obscured for international investors, this work argues that a streamlining to international practice is required; therefore, the ownership of the trust property under the shipping fund in China should be transferred to the trustee from the client. The trustee shall possess, employ, benefit, and dispose the trust property in his/her own name, which links up with China's current property legislation, ship registration, and ship arrest regulations. The trust property under the shipping fund in China is independent of the fixed property or other management property of the trustee, the beneficiary, and the custodian. This gives full play to functional advantages of the trust system of the shipping fund, contributes to the expansion of financing channels in the shipping industry in China, guarantees the specialization and flexibility of shipping investment activities and the diversity of the investment subject, promotes development of China's policies about the shipping industry and financial innovation, and boosts the realization of "The Strategy of National Revitalization Based on Marine Industry Development" and "The Belt and Road Initiatives" and construction of Shanghai International Shipping Center and International Finance Center.
Keywords: N25; L91; L92; L98; 330; alternative finance; China; green finance; one-belt-one-road; ship finance; shipping trust fund